Improving performance of eco-industrial parks. Issue 4 (3rd September 2017) - Layton, Astrid; Bras, Bert; Weissburg, Marc
Abstract: Industrial Ecology hypothesises that networks of industries designed to be analogous to the structure and properties of food webs may approach a similarly sustainable and efficient state. Although ecology is the metaphor for designing Eco-Industrial Parks (EIPs), prior research has shown that EIPs are inferior in performance compared to natural ecosystems. One EIP design approach is to enlarge EIPs by combining two or more synergistic networks to create a larger, and hopefully more successful, synergistic mega-network. A quantitative analysis using structural ecosystem metrics is presented in this paper in order to test the potential of this approach. The findings indicate that merely enlarging EIPs by significant amounts may not be the best strategy for improving performance, but that special attention should be placed on the inclusion of key actors like agriculture that act like detritivores and promote more intense internal cycling.